2011
DOI: 10.4161/auto.7.10.16818
|View full text |Cite
|
Sign up to set email alerts
|

Targeting autophagy enhances sorafenib lethality for hepatocellular carcinoma via ER stress-related apoptosis

Abstract: Fan (2011) Targeting autophagy enhances sorafenib lethality for hepatocellular carcinoma via ER stressrelated apoptosis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
271
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(284 citation statements)
references
References 32 publications
13
271
0
Order By: Relevance
“…However, the authors used a high concentration of sorafenib at 20 mmol/L (18). Even with the same concentration of sorafenib, another study showed that autophagy protected against sorafenib-induced cell death (20). Here, we have demonstrated that sorafenib at 10 mmol/L activated autophagy, which played a protective role against cell death of parental HCC cells, and is in agreement with a previous report (21); but exhibited a death-promoting role in sorafenib-resistant HCC cells.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the authors used a high concentration of sorafenib at 20 mmol/L (18). Even with the same concentration of sorafenib, another study showed that autophagy protected against sorafenib-induced cell death (20). Here, we have demonstrated that sorafenib at 10 mmol/L activated autophagy, which played a protective role against cell death of parental HCC cells, and is in agreement with a previous report (21); but exhibited a death-promoting role in sorafenib-resistant HCC cells.…”
Section: Discussionsupporting
confidence: 81%
“…Activation of autophagy is involved in the resistance to cisplatin (19), whereas inhibition of autophagy enhances the effect of sorafenib (20,21) in HCC cells. However, the role of autophagy and its cross-talk with other pathways in mediating resistance to sorafenib of HCC have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above described mechanisms, some limited studies have also demonstrated that EGFR [10] , glucose-regulated protein 78 (GRP78) [41] , multidrug resistance protein (MDRP) 2 [42] , nuclear factor κB (NF-κB) [43,44] and autophagy [45] may be involved in the acquired resistance to sorafenib in HCC.…”
Section: Hypoxic Microenvironment and Sorafenib Resistancementioning
confidence: 99%
“…13 Our results showed that SLC9A3R1 augmented LC3 foci in MDA-MB-231 cells (Fig. 1B and C), and the knockdown of SLC9A3R1 inhibited the starvation-induced increase in LC3 foci in MCF-7 cells (Fig.…”
Section: Slc9a3r1 Stimulates Autophagy In Breast Cancer Cellsmentioning
confidence: 80%
“…As described previously, 13 breast cancer cells were immediately fixed with 2.5% glutaraldehyde containing 0.1 mol/L sodium cacodylate and stored at 4 C. The samples were then embedded, and ultrathin (50 to 60 nm) sections were cut using an ultramicrotome (LEICA EM UC7, Wetzlar, Germany). The samples were examined with a JEM-1400 electron microscope (JEOL USA, Inc., Peabody, MA) at 80 kV, and the images were captured with a Veleta TEM camera (Olympus, Shinjuku, Japan).…”
Section: Electron Microscopymentioning
confidence: 99%